Factors influencing postnatal Option B+ participation and breastfeeding duration among HIV-positive women in Lilongwe District, Malawi: A qualitative study. - Valerie L Flax; Gloria Hamela; Innocent Mofolo; Mina C Hosseinipour; Irving F Hoffman; Suzanne Maman (PLoS ONE)
To ensure the health of mothers and children, prevention of mother-to-child HIV transmission (PMTCT) programs test women for HIV, engage HIV-positive women in care, and promote recommended breastfeeding practices. Under Malawi's Option B+ PMTCT program, ~20% of women are lost-to-follow-up (LTFU) and little is known about their breastfeeding practices. The purpose of this study is to describe facilitators and barriers to Option B+ participation and how participation influences breastfeeding duration. We conducted in-depth interviews with HIV-positive women in Option B+ (n = 32) or LTFU from Option B+ (n = 32). They were recruited from four government clinics in Lilongwe District and had a child aged 0-23 months. Women in Option B+ had better disclosure experiences and more social support than LTFU women. The most common reasons for LTFU were fear of HIV disclosure, anticipated or experienced stigma, and insufficient social support. Other reasons included: non-acceptance of HIV status, antiretroviral therapy (ART) side effects, lack of funds for transport, and negative experiences with clinic staff. Worries about possible transmission, even while on ART, influenced timing of weaning for some women in Option B+. Despite their knowledge of the risk of HIV transmission to the child, most LTFU women continued to breastfeed after stopping ART because they considered breastmilk to be an important source of nutrients for the child. Given that HIV-positive Malawian women LTFU from Option B+ breastfeed in the absence of ART, efforts are needed to use evidence-based strategies to address the barriers to Option B+ participation and avert preventable transmission through breastmilk.